Optimum Design of Retail and Wholesale Building for Minimum Energy Consumption and Total Cost - Watcharapongvinij, Anan; Therdyothin, Apichit (International Journal of Energy Economics and Policy, 2019)
The electric consumption in the building shares the highest portion in all user sectors. Therefore, energy conservation in building is important to get higher energy standard in the country. Retail and wholesale building consume high electricity. Energy consumption ratio in this building type is 40% Air conditioning, 28% Refrigeration, 12% lighting and 20% from the other. Those element need to be focused. This research is an optimization of air conditioning design and building envelope with operation schedule, refrigeration and lighting system. The objective is to find out optimization design to minimize total cost. The design criteria is to maintain requirement at day time whereas to response refrigeration system at all night. The developed designed is interacted between building system and building envelop. Case study is retail and wholesale building in Thailand. The design with life time of the machine, replacement cost and energy consumption of each option will be used to evaluate total life cycle cost. This study results in the total life cycle cost of new model of 1,014.14 M Baht comparing with 1,207.91 M Baht of conventional design. It has been saved 193.76 M Baht or 16% for 30 years. Therefore, the benefit of new improvement is very high and helps building owner to save a huge amount of money. Keywords: Optimization design; Retail and wholesale building; Energy saving in retail and wholesale building JEL Classifications: Q4 DOI: https://doi.org/10.32479/ijeep.8693